2017
DOI: 10.1073/pnas.1708321114
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling regulates ciliary localization of mouse odorant receptors

Abstract: The ciliary localization of odorant receptors (ORs) is evolutionary conserved and essential for olfactory transduction. However, how the transport of ORs is regulated in mammalian olfactory sensory neurons is poorly understood. Here we demonstrate that odorant responsiveness and OR transport is regulated by the Hedgehog pathway. OR transport is inhibited by conditional gene inactivation of the Hedgehog signal mediator Smoothened (Smo) as well as by systemic administration of the Smo inhibitor vismodegib, a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Primary cilia are widely found in many cells, including neural cells and blood cells, operating as cellular antennae for development via Sonic hedgehog (Shh) signaling [3943]. Shh in the olfactory mucus and epithelium is involved in axon growth, ciliary extension and functional localization of AC3 and odorant receptors in the cilia, though the loss of Shh is irrelevant to OMP expression [4447]; OMP is initially expressed before the functional maturation of ORNs. Unlike other terminally differentiated neurons, ORNs periodically undergo turnover [48], and OMP remains in the ORNs, even during the apoptotic stage [49].…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilia are widely found in many cells, including neural cells and blood cells, operating as cellular antennae for development via Sonic hedgehog (Shh) signaling [3943]. Shh in the olfactory mucus and epithelium is involved in axon growth, ciliary extension and functional localization of AC3 and odorant receptors in the cilia, though the loss of Shh is irrelevant to OMP expression [4447]; OMP is initially expressed before the functional maturation of ORNs. Unlike other terminally differentiated neurons, ORNs periodically undergo turnover [48], and OMP remains in the ORNs, even during the apoptotic stage [49].…”
Section: Discussionmentioning
confidence: 99%
“…Our results now suggest a role for motile cilia in noncanonical HH signaling. In addition, a recent report suggested the HH signaling components localize odorant receptors in mouse olfactory cilia ( 48 ); olfactory cilia have a 9 + 2 axoneme, but lack dynein arms and are immotile ( 30 ). Thus, during evolution, HH signaling components and cilia may have been adapted for a variety of functions, with variations in cilia type and the function of HH signaling components.…”
Section: Discussionmentioning
confidence: 99%
“…Non-canonical Wnt maintains basal NMDAR mediated synaptic transmission via the tyrosine kinase-like orphan receptor 2 (RoR2) (Cerpa et al 2015). Hh-signaling in the olfactory system can regulate the expression of olfactory receptors both in adult fruit fly, Drosophila Melanogaster, and in adult mice (Sanchez et al 2016, Maurya et al 2017. (Hall et al 2014).…”
Section: Morphogens In the Developed Nervous System Focus On Hedgehogmentioning
confidence: 99%
“…Additionally, the effect of Hh signaling on immature hippocampus has revealed that Hh promotes growth of presynaptic terminals and increasing the frequency of spontaneous vesicle release (Mitchell et al 2012). In adult fruit flies, Drosophila Melanogaster, Hh-signaling regulates the surface expression of odorant receptors in the fly antenna (Sanchez et al 2016) and controls the expression of odorant receptors and the odorant response in adult mice olfactory system (Maurya et al 2017). These findings triggered our interests to investigate if Hh-signaling could regulate receptor expression in mature central neurons as in the olfactory system.…”
Section: Paper IVmentioning
confidence: 99%